Thermodynamic analysis of an ammonia-water solution cross-type absorption-resorption heat pump system. (5th November 2021) - Feng, Lijie; Jin, Zhenghao; Zhou, Runfa; Xu, Mengkai; Qin, Luwen; Li, Shuhong
Highlights: The cross-type design is first proposed for the absorption-resorption heat pump. The gas-emission range and mass transfer potential of the system are enhanced. The performance and working temperature range of the system are increased. The system is appropriate for applications with larger pressure differences. Abstract: Absorption-resorption heat pump (ARHP) can realize the efficient utilization of low-grade heat under lower operating pressure than traditional absorption heat pump (AHP), but the application is limited by the low coefficient of performance (COP). In this paper, an ammonia-water solution cross-type absorption-resorption heat pump is proposed to improve the performance, and the rectifier can be eliminated because the ammonia component can be balanced with the adjustment of mass flow rate at the resorber inlet. A thermodynamic model is established to investigate the influences of different parameters on the coefficient of performance. The results reveal that: When the high/low pressure pair is 1.5/0.44 MPa and the temperatures of absorber, resorber and desorber are 40 °C, 40 °C and 5 °C, the COP of the proposed system can reach 1.564, which is 8.1% higher than traditional ARHP. When the temperatures of generator, absorber, resorber and desorber are 115 °C, 35 °C, 40 °C and 5 °C, the COP is improved up to 6.4% compared with the balanced-type ARHP. Besides, the proposed system has wider working temperature ranges than the traditional system and the temperature ranges of absorber and desorber are increased by 1 °C and 2 °C, respectively. The advantages of the proposed system also include the lower optimal low-pressure values. Therefore, the ammonia-water solution cross-type absorption-resorption heat pump is appropriate for working in larger pressure differences and makes waste heat recovery more economical and efficient.